DIMENSIONS OF A MEMORABLE FOOD AND RESTAURANT EXPERIENCE IN MOUNTAINOUS DESTINATIONS: AN INTERPRETIVE STRUCTURAL MODELING APPROACH - Devkant Kala (Enlightening Tourism: A Pathmaking Journal)
The present study attempts to determine the factors of memorable food and restaurant experience (MFRE) and model the interrelationships among them using interpretive structural modeling (ISM) in the mountainous destination. Variables of MFRE were identified through literature review, discussion with tourism & hospitality academicians and practitioners, and tourists visited the mountainous destinations of Uttarakhand, India. The results reveal that restaurant location, decoration, and service employee attributes were bottom-level variables in the model. Service quality, authentic local food, traditional food preparation, and hygiene & cleanliness were considered as middle-level variables. Authentic food presentation, food quality, and Physical environment experience were top-level variables in MFRE. This work endorses that destination restaurants should offer authentic foods, engage visitors with traditional food preparation & presentation, focus on food and service quality, maintain the hygienic servicescape, concentrate on staff appearance, decoration, and restaurant location to deliver memorable food and restaurant experience (MFRE) in the mountainous destinations.